Recitation of the Qur'an as a Spiritual Medium for Creating Inner Peace: A Case Study of Female Students - Nurdiani, Nurdiani; Mahmud, Salami; Jannah, Miftahul; Meutiawati, Ida (TAFSE: Journal of Qur'anic Studies, 2025)
This study examines how Qur’an recitation fosters inner peace among female students at Dayah Athiyah Banda Aceh. Despite growing evidence on the psychological benefits of Qur’anic practices, limited research has explored how daily recitation operates as a structured psycho-spiritual process within Islamic boarding schools, especially from the perspective of female students. Addressing this gap, the study employed a qualitative case study involving six students and one teacher, using in-depth interviews, observations, and documentation, with data analysed through Braun and Clarke’s reflexive thematic analysis. Three analytical themes were identified: emotional regulation through rhythmic recitation, which captures how tilawah reduces anxiety and stabilizes affect; cognitive centering for learning readiness, which reflects improvements in focus, mental clarity, and memorization preparedness; and spiritual anchoring and transcendental meaning-making, which highlights students’ experiences of divine connection, gratitude, and strengthened faith. Collectively, these themes show that Qur’an recitation functions as an integrated form of psycho-spiritual regulation shaped by the religious environment of the pesantren. The study contributes to existing literature by demonstrating how daily tilawah can serve as a structured model of Tilawah-Based Spiritual Therapy that supports emotional, cognitive, and spiritual well-being among female students.